Combining antimalarial drugs and vaccine for malaria elimination campaigns: a randomized safety and immunogenicity trial of RTS, S/AS01 administered with dihydroartemisinin, piperaquine, and primaquine in healthy Thai adult volunteers. Issue 1 (2nd January 2020) - von Seidlein, Lorenz; Hanboonkunupakarn, Borimas; Jittamala, Podjanee; Pongsuwan, Pongphaya; Chotivanich, Kesinee; Tarning, Joel; Hoglund, Richard M.; Winterberg, Markus; Mukaka, Mavuto; Peerawaranun, Pimnara; Sirithiranont, Pasathorn; Doran, Zoe; et al.
ABSTRACT: Introduction : RTS, S/AS01 is currently the most advanced malaria vaccine but provides incomplete, short-term protection. It was developed for use within the expanded program on immunizations (EPI) for African children. Another use could be adding mass RTS, S/AS01 vaccination to the integrated malaria elimination strategy in the Greater Mekong Subregion (GMS), where multidrug-resistant P.falciparum strains have emerged and spread. Prior to evaluating RTS, S/AS01 in large-scale trials﻿ we assessed whether the vaccine, administered with and without antimalarial drugs, is safe and immunogenic in Asian populations. Methods : An open-label, randomized, controlled phase 2 trial was conducted in healthy, adult Thai volunteers. Seven vaccine regimens with and without antimalarial drugs (dihydroartemisinin-piperaquine plus a single low dose primaquine) were assessed. Antibody titres against the Pf CSP full-length (NANP) 6, Pf CSP anti-C–term, Pf CSP full-length (N + C-Terminal) were measured by standard enzyme-linked immunosorbent assays. Liquid chromatography was used to measure piperaquine, primaquine and carboxy-primaquine concentrations. Results : 193 volunteers were enrolled and 186 study participants completed the 6 months follow-up period. One month after the last vaccination all study participants had seroconverted to the Pf CSP (NANP)6, and the Pf CSP Full Length (N + C-Terminal). More than 90% had seroconverted to the Pf anti-C-Term CSP. There was no indication that drug concentrations were influenced by vaccine regimens or the antibody levels by the drug regimens. Adverse events were similarly distributed between the seven treatment groups. No serious adverse events attributable to the study interventions were detected. Conclusion : This study found that RTS, S/AS01 with and without dihydroartemisinin-piperaquine plus a single low dose primaquine was safe and immunogenic in a healthy, adult Asian population.